Membedah Teologi Ahmadiyah : Kajian Kritis Atas Kepercayaan, Sejarah, dan Respons Umat Islam - Nur As’ad HL, Muh; Santalia, Indo; Aderus, Andi; Syamsu Rijal, Tabhan (Zawiyah: Jurnal Pemikiran Islam, 2025)
Studying Ahmadiyya is important for understanding the complexity of religious dynamics within contemporary Muslim societies. Analyzing the teachings and practices of Ahmadiyya provides insights into existing theological and sociological differences. This study aims to: First, examine the concept of Ahmadiyya’s beliefs and theological doctrines. Second, investigate the historical development of Ahmadiyya from its founding to its spread across the Islamic world. Third, explore the responses of Muslims both scholars and religious organizations toward the existence and teachings of Ahmadiyya. This research adopts a qualitative approach using the method of library research. The data sources consist of secondary materials including academic books, journal articles, religious fatwas, and other publications that discuss Ahmadiyya from external perspectives. The findings of the study reveal the following: First, Ahmadiyya holds a concept of prophethood that differs from that of the majority of Muslims. They believe that prophethood in Islam did not completely end with the Prophet Muhammad (peace be upon him). Ahmadiyya also has a different understanding of divine revelation, asserting that divine revelation can still be received by chosen individuals, particularly those who attain a high level of spirituality. Second, this study traces the origins of the Ahmadiyya movement from the colonial period in India to its expansion in various Muslim countries. Third, Muslim responses to the existence of Ahmadiyya are generally diverse, but most tend to show significant rejection. Many traditional Islamic scholars and religious organizations consider Ahmadiyya teachings to be a deviation from orthodox Islamic doctrine.